Coital emergencies. Issue 853 (November 1996) - Banerjee, A.
Abstract : The act of heterosexual coitus is associated with morbidity due to a variety of conditions as well as with a small risk of sudden death. Awareness of the presentation of coital emergencies is essential to allow appropriate medical management and sexual counselling.